How Does Financial Literacy Influence the Financial Growth of Microfinance Clients? - Khadka, Kamal Kumar (Journal of Nepalese Management and Research, 2025)
The primary objective of this study was to evaluate the effect of financial literacy on financial growth. It employed a descriptive and causal-comparative research design with a deductive approach. Primary data was gathered using a Likert scale from 385 microfinance clients in Rolpa District, Nepal, through a non-probability convenience sampling technique. Descriptive analysis and Pearson correlation analysis was conducted. To assess the influence of financial literacy on financial growth, multiple linear regression models were applied. The findings revealed that the independent variables accounted for 59.60 percent of the variation in the dependent variable, demonstrating a significant link between financial literacy and financial growth. The results showed that all independent variables played a significant role in driving financial growth and influencing the financial development of microfinance members. Each independent variable demonstrated a positive relationship with the dependent variable. Specifically, financial knowledge, financial behavior, and financial training concluded a positive and statistically significant influence on financial growth. These findings highlight the importance of these factors in promoting financial growth, emphasizing that enhancing financial literacy and behaviors can significantly contribute to the financial success of microfinance clients. Thus, the study underscores that financial literacy serves as a key driver of financial growth and plays a crucial role in its enhancement. It provides valuable insights for policymakers, researchers, microfinance institutions, microfinance clients, and other stakeholders to improve financial growth and make informed decisions regarding financial literacy initiatives in Nepal.